Analysis of Rockwood et Al's Clinical Frailty Scale and Fried et Al's Frailty Phenotype as Predictors of Mortality and Other Clinical Outcomes in Older Patients Who Were Admitted to a Geriatric Ward - Ritt, M.; Schwarz, C.; Kronawitter, V.; Delinic, A.; Bollheimer, Cornelius; Gaßmann, Karl-Günter; Sieber, Cornel (Journal of Nutrition, Health & Aging, 2015)
There are few data regarding the accuracy of short frailty tools as predictors of mortality and other clinical outcomes of older patients admitted to a geriatric ward. We therefore analyzed the accuracy of Rockwood et al's Clinical Frailty Scale and an easy and quick to perform operationalization of Fried et al's frailty phenotype, as predictors of mortality and other clinical outcomes in our cohort of patients.Prospective analysis with a follow-up period of 6 months.307 patients who were 65 years of age or older were included in the study. The patients were assessed in terms of the two frailty measures during their stay in a geriatric ward.The Clinical Frailty Scale and the frailty phenotype were both suitable for differentiating between patients who died due to any cause from those who survived during follow-up (primary outcome) (area under the ROC curves (AUC) values 0.867 (95% CI 0.807-0.926), p<0.001 and 0.754 (95% CI 0.688-0.821), p<0.001, respectively). Regarding the secondary outcomes: 1. unplanned admission to hospital and 2. a fall during follow-up, the Clinical Frailty Scale discriminated or tended to discriminate between patients to whom these criteria applied and those to whom they did not (AUC=0.569 (95% CI 0.502-0.636), p=0.046 and AUC=0.574 (95% CI 0.501-0.647), p=0.071, respectively). The frailty phenotype did not show such a differentiation when applied to secondary outcomes (AUC=0.500 (95% CI 0.432-0.568), p=0.994 and AUC=0.518 (95% CI 0.439-0.598), p=0.658, respectively).Both short frailty instruments are suitable predictors of mortality in older patients who were admitted to a geriatric ward. The Clinical Frailty Scale, but not the frailty phenotype, predicted at least some of the secondary outcomes, i.e., the outcome unplanned admission to hospital during follow-up.
EVALuna2:10581